THE CONSUMER BEHAVIOR UNDER THE PANDEMIC UNCERTAINTY: ANALYSIS OF THE EMPIRICAL FINDINGS IN GLOBAL CONTEXT - Amalia DUTU; Mihaela DIACONU; Daniela PIRVU; Olimpia OANCEA; Mihaela BRINZEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2020)
During the last year the consumer behavior was alternated under various factors, one of these being the uncertainty generated by the global health crisis. The Covid pandemic affected all the aspects of people’s life – economic security of the household, job security, income security, social relationship, physical and mental heat, social isolation and so on. In this context of economic and social shits, it is very important for business survival to understand how consumers changed there behaviors, and how these change will persist for a long time. Thus, the purpose of this study is to emphasis some of the most important behavior shifts since the first months from the pandemic start, considering different national contexts in which surveys were conducted and to presents the most important aspects of a crisis – the uncertainty and risk – the two elements with important impact on consumer behavior